Enrichment determination of low – enriched uranium material by gamma spectroscopic method - Bui , Van Loat; Nguyen , Van Quan; Le , Tuan Anh; Nguyen , Van Bay; Bui , Thi Hong; Nguyen , Cong Tam (Nuclear Science and Technology, 2014)
In this work the non - destructive gamma spectroscopic method for determination of uranium enrichment is presented. In order to determine the uranium enrichment the activity ratios of 234U/235U and 238U/235Uwere measured. The activity ratios234U/235U and 238U/235U were determined by using intrinsic efficiency calibration. As a test of this method, low - enriched uranium standard was measured, the obtained result was in good agreement with the estimated value.